2014
DOI: 10.1097/fjc.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pharmacologic Inhibitor of the NLRP3 Inflammasome Limits Myocardial Injury After Ischemia–Reperfusion in the Mouse

Abstract: Background The formation of the NLRP3 inflammasome in the heart during AMI amplifies the inflammatory response and mediates further damage. Glyburide has NLRP3-inhibitory activity in vitro, but requires very high doses in vivo, associated with hypoglycemia. The aim of this study was to measure the effects on the NLRP3 inflammasome of 16673-34-0, an intermediate substrate free of the cyclohexylurea moiety, involved in insulin release. Methods and Results We synthetized 16673-34-0 (5-Chloro-2-methoxy-N-[2-(4-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
176
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(186 citation statements)
references
References 17 publications
7
176
2
1
Order By: Relevance
“…40 This is in agreement with the observation that inflammasome activation of cardiac fibroblasts is essential for myocardial ischemia/reperfusion injury: 99 inhibition, silencing, or genetic deletion of NLRP3 in the mouse limited the infarct size in experimental acute myocardial infarction. [100][101][102] Intracerebroventricular injection of different pro-caspase-1 inhibitors was shown to protect against ischemic injury up to 7 days after induction of cerebral ischemia in rodents 31,103,104 and NLPR1 inhibition by the use of a blocking antibody demonstrated protective effects in a thromboembolic model 24 hours after induction of cerebral ischemia. 3 Accordingly, NLRP3 deficiency protects against experimental stroke: NLPR3-knockout mice have reduced infarct volumes, and there was reduced neuronal death in vitro, when co-incubated with OGD (oxygen glucose deprivation)-treated microglial cells with reduced NLRP3 expression.…”
Section: In Vivo Evidence For the Significance Of The Inflammasome Inmentioning
confidence: 99%
“…40 This is in agreement with the observation that inflammasome activation of cardiac fibroblasts is essential for myocardial ischemia/reperfusion injury: 99 inhibition, silencing, or genetic deletion of NLRP3 in the mouse limited the infarct size in experimental acute myocardial infarction. [100][101][102] Intracerebroventricular injection of different pro-caspase-1 inhibitors was shown to protect against ischemic injury up to 7 days after induction of cerebral ischemia in rodents 31,103,104 and NLPR1 inhibition by the use of a blocking antibody demonstrated protective effects in a thromboembolic model 24 hours after induction of cerebral ischemia. 3 Accordingly, NLRP3 deficiency protects against experimental stroke: NLPR3-knockout mice have reduced infarct volumes, and there was reduced neuronal death in vitro, when co-incubated with OGD (oxygen glucose deprivation)-treated microglial cells with reduced NLRP3 expression.…”
Section: In Vivo Evidence For the Significance Of The Inflammasome Inmentioning
confidence: 99%
“…This resulted in a marked decrease in cell damage (troponin I levels) and infarct size after 24 h [136] and reduced LV dysfunction after 7 days [137]. Additionally, the NLRP3 inhibitor reduced LV dysfunction and remodelling in mice 1 week after permanent LAD ligation without affecting infarct scar size [137].…”
Section: Nod-like Receptors and The Inflammasomementioning
confidence: 99%
“…Interestingly, a novel small molecule inhibitor of NLRP3 inflammasome formation has been developed (16673-34-0) that can reduce caspase-1 activity in the heart by >90% in mice subjected to experimental MI with reperfusion [136]. This resulted in a marked decrease in cell damage (troponin I levels) and infarct size after 24 h [136] and reduced LV dysfunction after 7 days [137].…”
Section: Nod-like Receptors and The Inflammasomementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we congratulate them for developing a novel pharmacological inhibitor of NLRP3 inflammasomes. According to their report, 2) they synthesized 16673-34-0 (5-chloro-2-methoxy-N-[2-(4-sulfamoylphenyl)-ethyl]-benzamide), an intermediate in the synthesis of glyburide, that is free of the cyclohexylurea moiety involved in insulin release, and found that this compound almost completely inhibited ATP-induced IL-1β secretion in J774 macrophages and ATP-induced caspase-1 activation and cell death in HL-1 cardiomyocytes in vitro. This NLRP3 inhibitor also reduced caspase-1 activation and infarct size in a murine model of myocardial ischemia-reperfusion (I/R) injury in vivo.…”
mentioning
confidence: 99%